PENGARUH PENDIDIKAN PELATIHAN DAN KESEJAHTERAAN TERHADAP PRODUKTIVITAS KERJA KARYAWAN (Studi Kasus pada PT. X Desa Sidareja Kabupaten Purbalingga) - Rika Rahayu; Ajeng Sekar Dini (Jurnal Akuntansi Dan Manajemen, 2022)
This study aims to identify the Effect of Village Fund Implementation and Village Program Effectiveness on the Quality of Human Resources in Margokatan Village and Margoluwih Village, Seyegan District, Sleman Regency. The type of data used is primary data obtained through the distribution of questionnaires with a google form. Respondents are the people of Margokatan Village and Margoluwih Village. The total number of respondents obtained was 101 people. The data were processed using multiple linear regression analysis techniques and using SPSS. The results of the study show that (1) the implementation of the Village Fund has a positive effect on the Quality of Human Resources in Margokaton Village and Margoluwih Village, Seyegan District, Sleman Regency, (2) Village Program Effectiveness has a positive effect on the Quality of Human Resources in Margokaton Village and Margoluwih Village, Seyegan District, Sleman Regency.